Adaptive Modulation and Coding With LDPC Codes and Retransmission for Ultraviolet Communication - Fei Long; Jingyin Tang; Lingfeng Li; Jingyang Chen; Chen Gong; Zhengyuan Xu (IEEE Photonics Journal, 2024)
To adapt to different transmission power and distances, we design a rate-compatible transmission protocol to realize different transmission rates for ultraviolet (UV) communication. We have designed ensembles based on low-density parity-check (LDPC) codes, incorporating various code lengths and rates working under different channel conditions. Furthermore, the direct sequence spreading technique is adopted to obtain different channel codes working in weaker channel conditions. Through simulating the frame error rate (FER) performance across various signal and background radiation intensities, we obtain a table of switching thresholds for channel coding under distinct channel conditions. Different from that for radio-frequency (RF) communication with only one parameter of signal-to-noise ratio (SNR), the switching threshold table is constructed based on the combination of two parameters for UV Communication, the signal intensity and background radiation intensity. We also propose adaptive coding with hybrid automatic retransmission requests based on the combination of signal intensity and background intensity. It is verified through simulation that our designed system shows larger throughput under varying channel conditions compared with channel coding with a fixed rate in UV Communication.